191. Commissioning of a high definition multileaf collimator with flattening filter free photon beams. (December 2018) - Manco, L.; Tonini, E.; Fabbri, S.; Turra, A.
Abstract: Purpose: Apex is a micro multileaf collimator mounted on the Elekta Versa HD. It has 56 leaf pairs with leaf thickness of 2.46 mm at isocenter and maximum field size of 12 × 14 cm 2 . Apex has been commissioned on treatment planning system (TPS) Pinnacle 9.10 for high dose rate stereotactic treatment using volumetric modulated arc therapy (VMAT) technique in conventional (6/10 MV) and flattening-filter free energies (6FFF/10FFF). Methods: All measurements were done according the request of the TPS[1] : Percentage Dose Depth, Profiles, Output factor, Absolute dose with PTW MP3-M water tank phantom using a synthetic diamond detector (PTW microdiamond 60019) and ionization chamber (PTW Farmer 30013, PTW Semiflex 31010)[2] for field dimension showed in Fig. 1; the validation of TPS model, was carried out by comparing calculated and measured doses acquired in water phantom for different source surface distance (SSD), detector depth and field configuration. Leaf leakage and transmission test was evaluated with PTW Octavius SRS 100. A comparison with multileaf Agility has been done. Results: Comparison between Agility and Apex showed an average reduction of 25%. Discrepancies between calculated and measured dose were in tolerance, 2% or 3%, according the complexity of the geometry. Mean intra leaf transmission were 0.31% and 0.40% (6/10 MV FFF). Mean inter leaf leakage were 0.32% for 6 MV FFF and 0.39% for 10 MV FFF. Conclusions: The high resolution of multileaf gives dosimetric advantages in penumbra of profiles and less dose outside the filed, thanks to smaller leaves double focused (Table 1 ). Unfortunately, there is few literatures on this specific topic so our experience could be useful to other center starting a similar commissioning. The time needed to mount the micromultileaf and manual fine tuning takes several minutes. Must be taking account several electronic troubles of this technologies with high dose FFF delivered during a commissioning.